Spatial Environment of Home, Stress Management, and Welfare of Family Living in Two-Level Marginal Regions - Euis Sunarti; Nurul Fatwa; Zulfa Rahmawati; Winny Faramuli; Dwifeny Ramadhany (Journal of Family Sciences, 2021)
This study aims to analyze the home environment, stress management, and families' welfare in marginal areas. The study design was cross-sectional, and samples were selected by random cluster sampling, as many as 126 families consisting of 63 families from the very dense region (VDR> 200 people per Ha) and 63 families from a rather dense region (RDR, 121-160 people per Ha) in Bogor, West Java, Indonesia. The data were collected by interview using a questionnaire in March and April 2014 and analyzed using descriptive and comparison tests. The analysis showed that families in RDR had a lower density but had a higher crowd level than in VDR, so that families in RDR had to try harder to get non-physical privacy. RDR families had a higher source of stress, thus encouraging them to did more coping strategies. The analysis showed that families in RDR had higher objective well-being but lowered subjective welfare than families in VDR. Families in RDR had higher physical welfare and lowered social and psychological welfare than families in VDR. The research findings had implications for the importance of strengthening the family environment and developing research methodologies in the field of family ecology.